An Impact Analysis of Retrofit Shading and Double Skin Facade on Building Performance at the Glass Office of PT Pertamina Patra Niaga - ITJ Jakarta - Sumarno Sumarno; Tigor Wilfritz Soaduon Panjaitan; Andarita Rolalisasi (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
Modern office buildings with glass envelopes often encounter challenges in energy efficiency, particularly due to excessive reliance on artificial lighting during daytime and intensive use of cooling systems. This condition is occurred at the PT Pertamina Patra Niaga - ITJ Jakarta office building. The installation of window films and curtain blinds has made interior spaces darker, preventing optimal utilization of natural daylight and consequently increasing electricity consumption. Such conditions not only reduce energy efficiency but also compromise visual comfort for occupants. This study aims to analyze the impact of retrofit shading and the double skin façade (DSF) on daylighting performance, visual comfort, and energy efficiency. The research employed an existing condition analysis using the Sefaira plug in SketchUp software and Sefaira web model - energyplus to simulate and evaluate the effects of retrofitting on the glass office building. The findings reveal that the integration of retrofit shading and DSF significantly improves natural daylighting quality 2% underlit, 42% well lit, and 44% overlit. Visual comfort was enhanced by lowering indoor illuminance levels of ASE from 87% to 43% lux and sDA from 100% to 98% lux, aligning with recommended standards. Furthermore, annual electricity consumption decreased substantially, from 269 to 130 kWh/m² per year. In conclusion, retrofit shading and DSF provide effective passive design strategies that enhance daylight utilization, improve occupant comfort, and support energy conservation. This study serves as a preliminary investigation for future research on integrating multiple passive design strategies in office building retrofits.